Perancangan Company Profile Pertamina Lubricants Gresik Sebagai Media Promosi Dan Informasi - Irene Siwi Mimpang; Bayu Setiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
The Pertamina Gresik (PUG) Lubricant Production Unit is located on Jl. Harun Tohir et al. Pulo Pancikan. Gresik, East Java 61113. Pertamina Lubricants Gresik has a role in collecting information, data and documentation needed in this design. This role aims to provide information to stakeholders regarding the production flow and products produced by Pertamina Gresik lubricants. This marketing is also a strategic medium in improving the company's image. Research methods include presentation content analysis, surveys, discussions and interviews with Pertamina Gresik lubricant practitioners. The design results show that an effective company profile presentation can be an attractive promotional medium for the audience. Animated isometric visual elements which can ultimately become an interactive company profile presentation that has a positive impact on customer understanding and memory.